Die wonderbaarlike vermeerdering van brood (Matt 14:13–21 en par): Historiese kritiek in perspektief - Aarde, Andries van (Hervormde teologiese studies, 1986)
The miraculous multiplication of loaves (Mt 14:13–21 and par): Historical criticism in perspective Certain aspects of the historical critical method are applied to the doublet of the narration of the miraculous multiplication of loaves in the Gospels of Mark and Matthew. An offset is that a single tradition apparently lies beyond the doublet. Furthermore, that the first narrative has been moulded from out of a particularistic perspective within a Palestinian situation in early Christianity and the second from out of an universalistic perspective within 'n Hellenistic situation. Thirdly, that Mark in his redactional interpretation of the narration used these perspectives for the purpose of eucharistic catechesis. Matthew, on the other hand, reinterpreted Mark's usage, fashioned the doublet into a messianic meal and emphazised more explicitly the intermediary role of the disciples in the feeding of the crowd. The article's intention is to put the historical critical method in perspective against the accusation that this method is a threat to the church and reformational theology.